PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN AKUNTABILITAS PUBLIK TERHADAP KINERJA RSUD DJOELHAM BINJAI - Sitio, Kezia Dominika; Parhusip, Poltak Teodorus (Jurnal Ilmiah Akuntansi (JIMAT), 2023)
This study aims to prove Organizational Culture, Organizational Commitment and Public Accountability affect performance. The sample in this study was obtained using the proportionate stratified random sampling method with a total sample of 77 respondents. The data analysis technique used is descriptive analysis, data quality test, classical assumption test, multiple linear regression analysis and hypothesis testing using t test and f test with a significance level of 5% using SPSS 26. From the results of research using SPSS, it is known that the value of the coefficient of determination (Adjustid R Square) is 0.730. Organizational Culture, Organizational Commitment and Public Accountability together affect Performance by 73%. Based on the results of multiple linear regression analysis, it can be concluded that organizational culture has a significant positive effect on performance, organizational commitment has a significant positive effect on performance and public accountability has a significant positive effect on performance at the Djoelham Binjai Regional General Hospital. From the results of the t test, it was obtained that tcount > ttable (2,936 > 1,993) and sig < 0.05 (0.004 < 0.05). This means that Ha1 is accepted and H01 is rejected or in other words, Organizational Culture partially has a positive and significant effect on Organizational Performance. For the second variable, the results obtained where the value of tcount > ttable (2,941 > 1,993) and the value of sig < 0.05 (0.004 < 0.05). This means that Ha2 is accepted and H02 is Rejected or in other words Organizational Commitment partially has a positive and significant effect on Organizational Performance and the third variable is obtained where the value of tcount > ttable (6.869 <1.993) and the value of sig <0.05 (0.000 > 0.05) . This means that Ha3 is accepted and H03 is rejected or in other words Public Accountability partially has a positive and significant effect on Organizational Performance. The higher the organizational culture, organizational commitment and public accountability, the better the performance in the hospital.